The two recensions of "On free decision" - Grosseteste, Robertus (Auctores Britannici medii aevi, 2017)
Robert Grosseteste (c. 1168-1253), Bishop of Lincoln from 1235 to 1253, was one of the most prominent and remarkable figures in thirteenth-century English intellectual life. He made a powerful impression on his contemporaries and subsequent thinkers at Oxford, and has been hailed as an inspiration to scientific developments in fourteenth-century Oxford. De libero arbitrio, his influential treatise on free will, was written between about 1225 and the early 1230s. This new edition contains Latin texts and en-face English translations of the two versions of the treatise. An extensive introduction provides a thorough account of Grosseteste's treatise, the sources of the text and also its uses in later writers such as Richard Rufus of Cornwall and Richard Fishacre. This book will be of interest not only to specialists in medieval philosophy and theology, but also to the general reader interested in free will